Synergistic Amylase and Debranching Enzyme Catalysis to Improve the Stability of Oat Milk - Xinyan Zhan; Jinye Zhang; Jiali Xing; Jinyi Xu; Dan Ouyang; Li Wang; Ying Wan; Xiaohu Luo (Foods)
Oat starch plays a crucial role in the stability of oat milk. Enzyme-hydrolyzed oat starch has been demonstrated to be an effective means of improving the stability of oat milk. The effects of different enzyme combinations on the stability of oat milk and the properties of starch in oats were investigated by adding α-amylase, amyloglucosidase, and different ratios of pullulanase and isoamylase. The results showed that as the degree of hydrolysis increased, the molecular weight, amylose content, and side chain length distribution of the starch decreased significantly. Moreover, compared with oat starch, the rheological and emulsifying properties of the starch hydrolysates were improved, and the characterization of emulsion stability showed that a 1:2 ratio of pullulanase to isoamylase promoted effective debranching and thus improved the stability of oat milk. This study demonstrated that debranching enzymes enhance the enzymatic hydrolysis of beverages and improve the physicochemical properties and stability of oat milk.